Implementation of Scaffolding Method to Improve Student Learning Outcomes on Praiseworthy Moral Material at MIS Asasul Islam - Sulaeman, Wono; Suryani, Yani; Faqori, Yudha Bima; Mawati, Yelmi (MANDAILING GLOBAL EDUKASIA, 2025)
Character education is essential in developing students’ morals, particularly in elementary schools. This study examines the implementation of the scaffolding method to improve learning outcomes on commendable morals among second-grade students at MIS Asasul Islam. Scaffolding is a teaching strategy that offers gradual support based on students’ needs, enabling them to understand concepts independently. The teacher acts as a facilitator by providing guidance, open-ended questions, and real-life examples relevant to students’ daily experiences. Using a qualitative descriptive approach, data were collected through observations, interviews, and analysis of student learning outcomes. The results show that the scaffolding method significantly enhanced students’ understanding of commendable morals. Indicators of improvement include increased student participation, the ability to apply moral values in everyday life, and higher test scores. Additionally, students demonstrated greater confidence in expressing opinions and reduced dependence on the teacher. The scaffolding method also contributed to a more interactive and student-centered learning environment, encouraging active engagement and boosting learning motivation. Students became more involved in building their own understanding, which supports the development of independent learning skills. Despite its effectiveness, the study found challenges in addressing diverse student abilities, requiring differentiated support strategies. Therefore, successful implementation demands careful planning and teacher expertise in adjusting the level of assistance. Overall, scaffolding is a promising method for enhancing character education in early learning settings.